Multidimensional evaluation of lighter gas dependency on a case of adhd: a case report - Özdemir Demirci, Esra; Özmen, Sevgi; Öztop, Didem Behice (Journal of Dependence, 2016)
Substance abuse and dependence is a major public health problem. Between adults as well as children and adolescents, the prevalence of drug use is increasing with each passing day; the age of substance use is falling steadily for years. Frequently seen diseases in childhood and adolescence, such as Attention deficit and hyperactivity disorder (ADHD), Conduct Disorder (CD) and various psychosocial factors increase the risk of substance abuse and addiction in children and adolescents. Abuse and addiction of inhalants and particularly lighter gas is becoming increasingly common because it is cheap and easily accessible, however, side effects are not known clearly. In the present case, it was aimed to draw attention to abuse and addiction of lighter gas which does not require legal obligations in taking.